The Chinese in Latin America and the Caribbean - Look Lai, Walton; Tan, Chee-Beng (Brill, 2010)
Written by specialists on the Chinese in Latin America and the Caribbean, this book tells the story of Asian migration to the Americas and contributes to a more comprehensive understanding of the Chinese in this important part of the world.